MENINGKATKAN KEMAMPUAN BERCERITA ANAK MELALUI METODE KARYA WISATA - WONDAL, ROSITA (Program Studi Magister Pendidikan Anak Usia Dini, 2015)
Abstract: Story telling is a form of articulation or language using words that are used to convey meaning Methods field trip is a way to present the material to the students learning by bringing the object to be studied outside the classroom. This study aims to determine the increase in ability to tell Charis Group B kindergarten children through tourist work methods. This type of research is classroom action research Subjects in this study were students in kindergarten early childhood Charis Group B with 15 students. The results showed that the method works can improve the ability to tell tour graders Gemia A kindergarten child's ability to tell the results of the first cycle that is 5 students who could tell the story well / completed (33.33%) and the second cycle increases, as many as 13 students or 86.67% of students of 15 students. so the increase is 53 340%. Keyword: Storytelling, Study Tour